Практичні аспекти бізнес-проектування як передумова торговельного підприємництва - Андрєєва, Лариса Олександрівна; Андреева, Лариса Александровна; Andrieieva, Larysa (Мелітополь: ТДАТУ, 2018)
UK: У статті обґрунтовано необхідність розробки бізнес-проектів для малого торговельного підп-риємництва. Розглянуто практичні аспекти бізнес-проектування, його особливості в малому торговельному підприємництві. Запропоновано основні структурні елементи бізнес-проекту щодо реалізації підприємницької ідеї на прикладі суб’єкту малого підприємництва. EN: Changing the economic conditions of the operation of business entities in a market pro-requires the constant examination of the external environment in order to determine the further directions of their development. This applies to the areas of trade sponsorship, where issues of business ideas implementation are very relevant. In for-eign practice, such programs have been called business projects. This necessitates a review of the practical aspects of developing and realizing business projects for commercial entrepreneurship.
Practical aspects of business design as a preferred trade entrepreneurship
Keywords: бізнес-проект; підприємництво; підприємницька ідея; конкуренція; прибуток; термін окупності; рівень рентабельності продажу; business project; entrepreneurship; business idea; competition; profit; payback period; the level of profitability of the sale